Oxford Dictionary of Chemistry - John Daintith (Oxford paperback reference, 2004)
"Containing many new entries as well as biographies of key scientists, it covers all aspects of chemistry, including physical chemistry and biochemistry. There are over 4,300 entries, including approximately 100 entries to this new edition. The dictionary also includes single- or double-page feature articles on important topics, such as polymers and crystal defects. Chronologies chart the main discoveries in such fields as atomic theory, biochemistry, explosives, and plastics"--Publisher description.